The role of kaempferol in gynaecological malignancies: progress and perspectives - Ma, Xijun; Zhang, Xiaoyu; Wang, Xuan; Wang, Congan; Ma, Yuning (Frontiers in Pharmacology, 2023)
Kaempferol, a flavonoid derived from various herbs such as cocoyam, propolis, and grapefruit, has garnered interest due to its numerous pharmacological benefits, including anti-inflammatory, antioxidant, and anti-diabetic properties. Kaempferol has been shown to possess notable anti-tumour bioactivity, indicating potential for treating gynaecological malignancies. To date, numerous studies have demonstrated the potential of kaempferol to induce tumour cell apoptosis, inhibit proliferation, and prevent metastasis and invasion in several gynaecological malignancies, including breast, ovarian and endometrial cancers. However, there is currently insufficient research investigating the efficacy of kaempferol for the treatment of gynaecological malignancies, and a lack of systematic review of its mechanism of action. Therefore, this review is founded on a literature analysis of the anticancer effects of kaempferol on gynaecological malignancies. The goal is to provide valuable reference material for scientific researchers and medical practitioners.